Role Of Low Dose Aspirin In Preventing Preterm Birth In Patients With Previous History Of Preterm Delivery - Maliha Sadaf; Aasia Saleem; Tallat Farkhanda; Khansa Iqbal; Sabeen Ashraf; Amna Iftikhar (Journal of Rawalpindi Medical College)
Objective: Preterm birth (PTB) occurs between 24-37 weeks of gestation. The important risk factor for PTB is a previous PTB and currently progesterone is used for the management of recurrent spontaneous PTB. Some studies have shown good outcomes but recent studies revealed that the use of vaginal progesterone was not related to a decreased likelihood of PTB or neonatal adverse effects. Thus, the controversy in the literature suggests multiple underlying pathological mechanisms involved in the progression of PTB. This study aims to determine the role of low-dose aspirin in the prevention of preterm birth in patients with a previous history of preterm delivery.